Excess pCO2 and carbonate system geochemistry in surface seawater of the exclusive economic zone of Qatar (Arabian Gulf) - Connor, Izumi (2022)
Dissolved inorganic carbon (DIC) and total alkalinity (TA) were sampled in December 2018 and May 2019 in the Exclusive Economic Zone (EEZ) of Qatar in the Arabian Gulf. pCO2, pH and CO32− were calculated from DIC and TA. TA, DIC and salinity increase in the Gulf due to evaporation after entering through the Strait of Hormuz. Temperature also increases. The pCO2 in surface seawater averaged 458 ± 62 which was higher than the atmospheric value of 412 ppm. Hence, the Gulf was a source of CO2 to the atmosphere. pCO2 in seawater is controlled by TA relative to DIC as well as temperature and salinity. A hypothetical model calculation was used to estimate how much pCO2 could increase in surface seawater due to various processes after entering through the Strait of Hormuz. Increases in T and S, in the absence of biogeochemical processes, would increase pCO2 to 537 μatm, more than enough to explain the high pCO2 observed. CO2 is lost from the Gulf due to gas exchange, decreasing DIC, and reducing pCO2 to 464 μatm, similar to that observed. The impact of biological processes depends on the process: calcification increases pCO2 while net primary production decreases pCO2. Salinity-normalized (to S = 40) total alkalinity (NTA) and dissolved inorganic carbon (NDIC) in surface seawater decrease as waters flow north from Hormuz. The slope suggests that removal of C as CaCO3, organic matter (CH2O) or gas exchange (FCO2) is occurring with a ratio of ΔCaCO3/(ΔCH2O or FCO2) = 1:2.86. The tracer Alk*, defined as the deviation of potential alkalinity (AP) (where AP = TA + 1.26 [NO3]) from conservative potential alkalinity ((ApC), (ApC = S Ap′S′ where A'P and S′ are mean values for the whole surface ocean) has values primarily determined by CaCO3 precipitation and dissolution. Its values in the Gulf ranged from −50 to −310 μmol kg−1 implying CaCO3 precipitation. The average value of ΔAlk*, the difference in Alk* between specific locations in the Qatari EEZ and the surface water entering through the Strait of Hormuz, was −130 μmol kg−1 which corresponded to a calcification of 65 μmol kg−1. Our model calculations indicate that this would increase pCO2 to 577 μatm. Carbonate forming plankton have not been observed in the water column suggesting that calcification occurs in corals, even though they have been severely damaged by past bleaching events. The amount of DIC removed by net primary production is small, consistent with an oligotrophic food web dominated by remineralization. It appears that the role of biological production in the water column for the control of pCO2 is very small. The high observed pCO2 reflects a balance between sources due to the impact of increasing T and S on the carbonate system equilibrium constants and net calcification and sinks due to CO2 loss due to gas exchange and net primary production in surface seawater after it enters the Gulf through the Strait of Hormuz.